KAJIAN EMPIRIS PENENTU NIAT PEMUDA UNTUK BERWIRAUSAHA DI DESA WISATA JATILUWIH KABUPATEN TABANAN - Suastini, Ni Made (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2020)
Entrepreneurship is indispensable for economic growth in Indonesia because entrepreneurship contains aspects of innovation, new ideas, creativity, and job creation. The purpose of this study was to determine how the entrepreneurial intentions of youth in the Jatiluwih Tourism Village, Tabanan Regency, Bali. The variables in this study are also expected to help identify and explain the factors that are considered in entrepreneurial intentions so that they are expected to help reduce unemployment in Tabanan Regency, Bali. The results of this research data analysis found that the variables of need for achievement, family support, and self-efficacy partially had a positive and significant effect on entrepreneurial intentions.